2019
DOI: 10.1101/617142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ETV4 is necessary for estrogen signaling and growth in endometrial cancer cells

Abstract: Estrogen signaling through estrogen receptor alpha (ER) plays a major role in endometrial cancer risk and progression; however, the molecular mechanisms underlying ER's regulatory role in endometrial cancer are poorly understood. In breast cancer cells, ER genomic binding is enabled by FOXA1 and GATA3, but the transcription factors that control ER genomic binding in endometrial cancer cells remain unknown. We previously identified ETV4 as a candidate factor controlling ER genomic binding in endometrial cancer … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 55 publications
(63 reference statements)
6
18
0
Order By: Relevance
“…In addition, our study focused on a particular endometrial cancer cell line, Ishikawa, and the effects of ESR1 mutations may be different in different models. We recently found that ESR1 genomic binding is consistent between endometrial tumors and distinct from breast tumors, with Ishikawa exhibiting a clear endometrial cancer ESR1 binding pattern (Rodriguez et al 2019a), suggesting that our findings could be generally applicable. In summary, our study has led to the creation of isogenic models of mutant ESR1 in endometrial cancer cells, the confirmation of estrogen-independent mutant ESR1 activity, and the discovery of novel gene regulation through mutant ESR1 that cannot be explained by constant activity alone.…”
Section: A B C Dsupporting
confidence: 51%
See 1 more Smart Citation
“…In addition, our study focused on a particular endometrial cancer cell line, Ishikawa, and the effects of ESR1 mutations may be different in different models. We recently found that ESR1 genomic binding is consistent between endometrial tumors and distinct from breast tumors, with Ishikawa exhibiting a clear endometrial cancer ESR1 binding pattern (Rodriguez et al 2019a), suggesting that our findings could be generally applicable. In summary, our study has led to the creation of isogenic models of mutant ESR1 in endometrial cancer cells, the confirmation of estrogen-independent mutant ESR1 activity, and the discovery of novel gene regulation through mutant ESR1 that cannot be explained by constant activity alone.…”
Section: A B C Dsupporting
confidence: 51%
“…The molecular consequences of ESR1 LBD mutations have not been explored in endometrial cancer and warrant investigation. We used a CRISPR/Cas9-mediated epitope tagging strategy called CETCH-seq (Savic et al 2015) in Ishikawa cells, an endometrial adenocarcinoma cell line that exhibits ESR1 genomic binding similar to endometrial tumor samples (Rodriguez et al 2019a), to model a common ESR1 LBD mutation, D538G. This technique combines guide RNAs that target Cas9 to the C terminus of ESR1 and a donor plasmid that leads to the incorporation of a 3X FLAG epitope tag and neomycin resistance gene at ESR1's endogenous locus ( Fig.…”
Section: Generation Of D538g Esr1 Mutant and Wild-type Cell Linesmentioning
confidence: 99%
“…Analysis of additional factors bound to these regions indicates that p300 is bound to CISH-2 and MMP17-1, the sites responsible for acetylation of the neighborhood. NFIC and ETV4 ( 35 ) were also uniquely found at CISH-2 and MMP17-1 as opposed to CISH-1 and MMP17-2. An expanded genome-wide analysis of ERBS, split by H3K27ac overlap, uncovered strong enrichment of EGR1, NFIC, MAX, TCF12, USF1, ETV4 and SRF at ERBS that overlap with H3K27ac compared to ERBS without H3K27ac.…”
Section: Discussionmentioning
confidence: 95%
“…ETV4, a member of the PEA3 subgroup of the ETS transcription factor family, 26 plays important roles in regulating gene expression during early embryogenesis, 27 obesity, and diabetes, 28 as well as oncogenesis, 29,30 and its overexpression is involved in the malignant transformation of cells and enhanced tumor cell invasion. 31,32 According to a recent study, ETV4 promotes the migration and metastasis of clear-cell renal-cell carcinoma in vitro and in vivo. 33 However, research studies on the expression of ETV4 in cervical cancer are rare.…”
Section: Discussionmentioning
confidence: 99%